Anterior segment changes following short‐term reading and its correlation with corneal biomechanical characteristics. (5th March 2013) - Niyazmand, Hamed; Ostadi Moghaddam, Hadi; Sedaghat, Mohammad Reza; Ahmadi Hosseini, Seyed Mahdi; Abolbashari, Fereshteh
Abstract Purpose To investigate the changes in anterior segment following short‐term reading and evaluate the correlation of such changes with corneal biomechanical characteristics (CBC). Methods Thirty‐six right eyes of 36 healthy subjects were examined. Anterior segment parameters were measured using the Pentacam before and after 30 min of reading. Ocular Response Analyzer was used to record CBC after reading. The following were recorded: central corneal thickness (CCT), central corneal power (CCP), superior corneal power (SCP), inferior corneal power (ICP), anterior chamber depth (ACD), anterior chamber volume (ACV), anterior chamber angle (ACA), corneal hysteresis (CH) and corneal resistance factor (CRF). Statistical analysis was performed with the paired student t‐test and Pearson correlation test in SPSS 16. Results There were statistically significant decreases in CCP, SCP, ACD and ACV values following reading (p < 0.05). Our results showed a statistically significant negative correlation between CH and changes in ICP (r = 0.36, p = 0.02). Significant negative correlations were also found between CRF and changes in ICP (r = 0.41, p = 0.01) and SCP (r = 0.34, p = 0.04). On the other hand, statistical analysis indicated no correlation between CBC and other studied parameters (p > 0.05). Conclusion This study demonstrated significant changes in some anterior segment parameters after reading. Being knowledgeable about these changes may have important implications in high accuracy examinations such as pre‐operative assessment of corneal refractive surgery candidates. This could also help researchers have a better understanding of the factors that may influence near work related development of refractive errors.